Limits on the effective quark radius from inclusive ep scattering at HERA - Foster, B; Cooper-Sarkar, A; Devenish, R; Gwenlan, C; ZEUS Collaboration (Elsevier, 2016)
The high-precision HERA data allows searches up to TeV scales for beyond the Standard Model contributions to electron–quark scattering. Combined measurements of the inclusive deep inelastic cross sections in neutral and charged current ep scattering corresponding to a luminosity of around 1 fb−1 have been used in this analysis. A new approach to the beyond the Standard Model analysis of the inclusive ep data is presented; simultaneous fits of parton distribution functions together with contributions of “new physics” processes were performed. Results are presented considering a finite radius of quarks within the quark form-factor model. The resulting 95% C.L. upper limit on the effective quark radius is 0.43⋅10−16 cm.